The Handbook of Crisis Communication 2010
DOI: 10.1002/9781444314885.ch9
|View full text |Cite
|
Sign up to set email alerts
|

How Do Past Crises Affect Publics' Perceptions of Current Events? An Experiment Testing Corporate Reputation during an Adverse Event

Abstract: Previous research in crisis communication has shown that a corporation's history of crises has a damaging effect on reputation during a current crisis. This study uses an experiment with student subjects testing not only the effect of a corporation's own crises on reputation, but also the reputational effect of a corporation without a crisis history but in an industry with a history of similar crises, called extraorganizational crisis history. Findings of this experiment show that publics' knowledge of extraor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Research in the field of global pandemic (i.e. Covid-19) and crisis communication has largely been dominated by the case study approach as the main methodology (An and Cheng, 2010;Elliot, 2010;Kelley, 2014;Claeys and Cauberghe, 2015).…”
Section: Methodological Trendsmentioning
confidence: 99%
“…Research in the field of global pandemic (i.e. Covid-19) and crisis communication has largely been dominated by the case study approach as the main methodology (An and Cheng, 2010;Elliot, 2010;Kelley, 2014;Claeys and Cauberghe, 2015).…”
Section: Methodological Trendsmentioning
confidence: 99%
“…Elliot (2010) found out the loss of reputation being the major damage to an enterprise and indicated that maintaining favorable image was a serious issue in various industries. Corporate crisis being exposed through the media would damage institution image, the mass regarding a company as a whole and an enterprise as a member of the society, including corporate image and store image, 2. functional image, the image generated from the operational activities in an enterprise management, containing service image and price image, and 3. commodity image, the attitudes of people towards the commodities or services provided by a company, covering brand image and product image.…”
Section: Corporate Imagementioning
confidence: 99%
“…A study of crisis communication is more oriented to external organizational crisis communication, namely relations between stakeholders/crisis-controlling organization and crisis-related organization or institution. For instance, research of organization protecting their reputation during a crisis (Elliot, 2010); the impact of media and spokesperson on stakeholders' response (Brown, & Billings, 2013); the strategy of crisis communication (Adamu, 2016); the management of communication disparities in identifying crisis between expert of the government and Non-Governmental Organization (Palttala, et al, 2012;Lestari et al, 2012); difference in the method of conveying information via social media between regional government and residents affected by disaster (Hong, et al, 2018); perception of social media use for crisis communication between the government and Non-Governmental Organization (Ly-Le, 2018); strategy of responding to crisis communication within a trade association (Frandsen & Johansen, 2018).…”
Section: Introductionmentioning
confidence: 99%